Diagnostic and Therapeutic Guidance for Class II Malocclusion Treatment - Anfal A Al-Ani (University of Mosul, College of Dentistry, 2013)
Aims: to detect the prevalence of PTID among our Class II sample and to establish a simple method to assess it, providing a diagnostic and therapeutic guidance for the Class II malocclusion treatment. Materials and methodes: The existence of (PTID) was investigated among 114 Class II div.I adults. Randomly selected 30 subjects from each group, adding 30 Class I subjects (as a control group) for cast and Cephalometric measurements. Resultes: Mandibular retrusion with posteriorly displaced mandible of normal size, was of functional mandibular retrusion, while this retrusion when caused by micrognathic mandible, was of anatomic mandibular retrusion. Conclusions: The relevance of these findings was stressed for the treatment planning of Class II subjects, confirming that controlling the transverse component of the occlusal patterns represent an additional input signal for the anteroposterior adjustment between the skeletal bases